Učinki vadbe na ravnotežni plošči Wii na ravnotežje pri starostnikih - Zupanc, Aleksander (Rehabilitacija (Ljubljana), 2015)
Background: Balance disorders are a risk factor for falling for the elderly people. Balance training can be achieved using games in virtual reality. The purpose of this systematic review was to determine if there was evidence that training on the Wii balance board improves balance in functionally independent elderly people. Method: Based on precise inclusion and exclusion criteria (randomized controlled trials involving functionally independent people aged over 60 years, without orthopaedic and neurologic disability and impaired perception), a systematic review of literature was conducted using the PubMed, CINAHL and PEDro databases. The quality of the included randomized controlled trials was assessed using the PEDro scale. Results: Five randomized controlled trials were included in the detailed review, which studied effects of training on the Wii balance board by one or more experimental and control groups. The participants were aged from 74.8 to 85.7 years on average, the sample size ranged from 12 to 58. The effects of balance training were measured using objective assessment tools. The training lasted for three, six, ten and twenty weeks. An improvement of balance after training was reported in all the studies; the largest balance improvement was achieved after a program combining exercises for muscle strength and balance with training on the Wii balance board. Conclusion: Training on the Wii balance board is feasible and safe for functionally independent elderly people, and it can be used as an additional to the standard exercises for balance and muscle strength for improving balance.
Keywords: Aged; balance; elderly; navidezna resničnost; Nintendo system; ravnotežje; sistem Nintendo; starejši; starostniki; virtual reality; Wii Fit